Business Strategy Model on the Optimism of MSME (Small Enterprises) Performance in the West Java Region Indonesia - Supriyati; Sri Mulyani; Harry Suharman; Taufiq Supriadi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to examine the business strategy model of UMKM Juara towards increasing optimism on the performance of MSMEs. The research method used is a qualitative method with a field approach, an institutional approach, and a library approach. The types of data used in this research are primary data and secondary data. Data collection techniques used are observation, interviews and literature study, while secondary data comes from journals, proceedings, government regulations, and legislation. The results of this study found that the business strategy model with the UMKM Juara concept resulted in an increase in various things such as MSMEs advancing to class, increasing income. This is because the UMKM Juara concept is digital-based, where MSMEs are fostered to be able to compete in the global market. Thus, the business strategy model must develop to digital based, so that improvements in MSME performance can be achieved.